A fully human IgG1 anti‐PD‐L1 MAb in an in vitro assay enhances antigen‐specific T‐cell responses. Issue 5 (20th May 2016) - Grenga, Italia; Donahue, Renee N; Lepone, Lauren M; Richards, Jacob; Schlom, Jeffrey
Abstract : Monoclonal antibodies (MAbs) that interfere with checkpoint molecules are being investigated for the treatment of infectious diseases and cancer, with the aim of enhancing the function of an impaired immune system. Avelumab (MSB0010718C) is a fully human IgG1 MAb targeting programmed death‐ligand 1 (PD‐L1), which differs from other checkpoint‐blocking antibodies in its ability to mediate antibody‐dependent cell‐mediated cytotoxicity. These studies were conducted to define whether avelumab could enhance the detection of antigen‐specific immune response in in vitro assays. Peripheral blood mononuclear cells from 17 healthy donors were stimulated in vitro, with and without avelumab, with peptide pools encoding for cytomegalovirus, Epstein–Barr virus, influenza and tetanus toxin or the negative peptide control encoding for human leukocyte antigen. These studies show for the first time that the addition of avelumab to an antigen‐specific IVS assay (a) increased the frequency of activated antigen‐specific CD8 + T lymphocytes, and did so to a greater extent than that seen with commercially available PD‐L1‐blocking antibodies, (b) reduced CD4 + T‐cell proliferation and (c) induced a switch in the production of Th2 to Th1 cytokines. Moreover, there was an inverse correlation between the enhancement of CD8 + T‐cell activation and reduction in CD4 + T‐cell proliferation induced by avelumab. These findings provide the rationale for the use of avelumab anti‐PD‐L1 in in vitro assays to monitor patient immune responses to immunotherapies. Immunotherapy: Detecting dormant defenders: An antibody targeting an immune protein may prove useful for studying patients' capacity to muster a defense against cancer or infection. The monoclonal antibody avelumab was developed to block PD‐L1, a protein that can inhibit the immune response to some cancers and disease. Some researchers have worried that it may also mark healthy immune cells for destruction, but findings from Jeffrey Schlom and colleagues at the US National Cancer Institute in Bethesda dispel these concerns. The researchers found that immune cells from healthy donors generally mounted a more robust response to viral proteins after treatment with avelumab, with increased activation of immune cells, which target both tumors and pathogens. The authors conclude that avelumab may offer a useful tool for assays to detect latent disease‐specific immune cells, which could then be stimulated to mount a therapeutic response.